The effect 8 weeks concurrent training on telomere length, telomerase activity and TRF2 in sedentary young men - yahya Mohammadnajad; hassan matinhomaee; Mohammad ali Azarbibijani (Shahid Beheshti University, 2019)
Purpose: Telomeres and their lengths have always been considered important biomarkers in the process of life. Shortening of telomere length and telomerase activity are strongly correlated with psychological stressors and risk factors, the aim of this study was to examine the effect of 8 weeks resistance- interval training on telomere length and telomerase activity in sedentary young men.Methods: Twenty sedentary young male students were selected and randomly assigned in to two groups of training (N=10) and control group (N=10). The mean age, weight and height of the subjects were: training group (21.9 ± 0.93, 78.38 ± 6.27, and 178.3 ± 48.3 cm, respectively) and control group (22.6 ± 0.33, Year, 72.13 ± 13.9 kg and 97.9 ± 6.21 cm). The protocol was running for eight weeks with three sessions a week. The duration of each training session was 80 minutes, the first part of which included a routine exercise routine on the tape, and the second part was a resistance training which determine for the training group. Blood samples 10 ml from the brachial vein of the subjects was taken half hour before the first training session and 24 hours after last training session. To measure the telomere length from Real time-PCR reaction, the TRAP method was used to measure the activity of telomerase enzyme and the ELISA method was used to measure TRF2. Independent and dependent t-test was used for data analysis and significance level in all tests was considered (P≤0.05).Results: Telomere length, telomerase activity, and TRF2 were significantly increased in the exercise group before and after exercise, but in the control group there was no relationship before and after the measurement. Independent t-test results showed a significant difference between the training and control groups in telomere length (t=3.87, p= 0.022), telomerase activity (t=5.10, p= 0.001), and TRF2 values (t=2.463, p= 0.014).Conclusion: Eight weeks of interval resistance training significantly increased the telomere length and telomerase activity of the subjects. Therefore, it seems that eight weeks of interval resistance training can have a beneficial effect on telomere biology and quality of life. The results indicated the importance of regular exercise activity with control aging and reduced the risk of disease associated with age. Regular exercise activity is also a potent inhibitor for telomeres length, telomerase activity, and Telomere Repeat Binding Factor2 (TRF2) protein expression.